HUBUNGAN PENGETAHUAN DAN SELF-EFFICACY DENGAN KESIAPSIAGAAN BENCANA PADA ANGGOTA KSR DI PMI JAKARTA - Yashinta Ariyanti (2022)
Indonesia is a country with a very interesting region. 65% of its territory consists of oceans and the rest is land. In addition, the dense population and reduced land use cause the area of water absorption to decrease. This causes Indonesia to become one of the countries with disaster-prone risks. When a disaster occurs, volunteers are needed to help prevent pre-disaster and post-disaster management. This has made many organizations appear, one of which is the Indonesian Red Cross (PMI). The purpose of this study was to determine the relationship between knowledge and self-efficacy with disaster preparedness among members of KSR PMI Jakarta. This research is a quantitative study with cross sectional design method. The sampling technique used is accidental sampling with 154 respondents. Data collection was done by distributing questionnaires through the g-form. The results showed that there was a relationship between knowledge (early warning, disaster triage and first aid) and self-efficacy with disaster preparedness (p < 0.05). Recommendations for further research are expected to be carried out with a qualitative approach because the research instrument is vulnerable to respondents' perceptions that do not describe the actual situation in each of them.